Nevsun Resources NSU ? TSX & AMEX Mission: To build a mining company taking exploration discoveries into production (Canadian Institute of Mining, Metallurgy and Petroleum, 2006)
TABAKOTO / SEGALA ? Annual gold production approximately 100,000 oz ? Debt free ? Unhedged ? Combined surface reserves 949,000 oz ? Combined 9 year life Tabakoto open pit reserve 568,000 oz (3.4m tonnes @ 5.26 g/t Au) Segala open pit reserve 381,000 oz (3.98m tonnes @ 2.98 g/t Au)